TRIP4 promotes tumor growth and metastasis and regulates radiosensitivity of cervical cancer by activating MAPK, PI3K/AKT, and hTERT signaling. (28th June 2019) - Che, Yilin; Li, Yizhuo; Zheng, Fufu; Zou, Kun; Li, Zongjuan; Chen, Manyu; Hu, Sheng; Tian, Chunfang; Yu, Wendan; Guo, Wei; Luo, Meihua; Deng, Wuguo; et al.
Abstract: Thyroid hormone receptor interactor 4 (TRIP4), a subunit of the tetrameric nuclear activating signal co-integrator 1 (ASC-1) complex, exerts pro-tumorigenic effects. The role for TRIP4 in the regulation of cervical cancer growth and radiation resistance is presently unknown. In this study, TRIP4 was found to be highly expressed in cervical cancer cells and tumor tissues. Knockdown of TRIP4 significantly suppressed cervical cancer cell proliferation and epithelial-mesenchymal transition (EMT), accompanied by inactivation of PI3K/AKT and MAPK/ERK signaling. TRIP4 was also found to target hTERT signaling by regulating its binding to the hTERT promoter. Moreover, the knockdown of TRIP4 increased cell sensitivity to radiation, concomitant with downregulation of Rad51 and p-H2AX. We also demonstrated in an in vivo study that the knockdown of TRIP4 effectively suppressed cervical cancer growth and progression in a xenograft tumor model, and these effects were concomitant with the downregulation of p-AKT, p-ERK, p-MEK1/2, MMP-9 and hTERT expression. Immunohistochemical analysis of tumor tissue microarrays showed that TRIP4 overexpression predicted poor prognosis in patients with cervical cancer. Collectively, these results show that TRIP4 plays an essential role in cervical cancer growth and survival. Highlights: TRIP4 promotes cervical cancer growth in association with activation of MAPK and PI3K/AKT signaling pathways. TRIP4 promotes the migration and invasion of cervical cancer cells. TRIP4 regulates hTERT to decrease radiosensitivity in cervical cancer cells. TRIP4 promotes cervical cancer progression in mouse model. TRIP4 promotes cervical cancer progression in clinical tissue samples.